(untitled) (Research, Society and Development, 2025)
The use of medicinal plants and the substances extracted from them is as old as the history of man itself. The evolution of medicines took place empirically, in processes of discovery through trials, errors and successes. In this sense, buriti (Mauritia flexuosa) is a palm tree from the Palmae family, widely distributed throughout tropical America, including the Northeast, North and Central-West regions of Brazil. Thus, buriti has a variety of popular uses for all its parts (roots, leaves, fruit and seeds) as raw material for medicinal and food use, craft furniture and shelter structures. The objective of the study was to evaluate the effects of Buriti oil (Mauritia flexuosa) on karyoallantoic membranes of embryonated chicken eggs, evaluating angiogenic and anti-angiogenic activities. The present study made it possible to understand the effects of the plant on angiogenic activity, with great importance for this relationship since there are no studies of Buriti oil from chorioallantoic membranes of embryonated chicken eggs. From this perspective, it was possible to obtain greater understanding and contribution to the development of future products with good social reach, mainly because it is a plant (renewable source), easily accessible and low cost. The results obtained showed that Mauritia flexuosa presents angiogenic activity, and that the test membranes presented excellent quality, meeting expectations when quantifying vascularization in each of the project stages.